Continuous and minimally-interrupted direct oral anticoagulant are both safe compared with vitamin K antagonist for atrial fibrillation ablation: An updated meta-analysis. (1st July 2018) - Ha, Francis J.; Barra, Sergio; Brown, Adam J.; Begley, David A.; Grace, Andrew A.; Agarwal, Sharad
Abstract: Background: The appropriate and safe peri-procedural anticoagulation schedule for patients on a direct oral anticoagulant (DOAC) undergoing AF ablation is not known. We aimed to evaluate the safety and efficacy of both continuous and minimally-interrupted novel oral anticoagulant (DOAC) strategies compared with uninterrupted vitamin K antagonist (VKA) for atrial fibrillation (AF) ablation. Methods: We searched electronic databases for randomized or prospective controlled observational studies comparing DOAC (continuous or interrupted) versus uninterrupted VKA. The primary endpoint was major bleeding. Secondary endpoints were total bleeding (composite of major and minor bleeding) and symptomatic thromboembolism. Data were analyzed by random-effects modeling and sensitivity analyses performed according to study design and peri-procedural DOAC schedule. Results: Thirteen studies (4 randomized, 9 observational) with 5463 patients were included in final analysis (45% on DOAC). DOAC was associated with less major bleeding compared with VKA in pooled randomized studies (odds ratio [OR] 0.27, 95% confidence interval [CI] 0.09–0.80, p = 0.03, I 2 = 0%), however there was no difference on overall analyses (OR 0.70, 95% CI 0.39–1.24, p = 0.22, I 2 = 27%). When stratified by DOAC dose schedule, there was no difference in major bleeding for continuous DOAC (OR 0.48, 95% CI 0.21–1.11, p = 0.09, I 2 = 6%) or minimally-interrupted DOAC (OR 0.81, 95% CI 0.37–1.76, p = 0.60, I 2 = 43%) compared with VKA. There was no difference between DOAC and VKA for risk of total bleeding ( p = 0.20) or symptomatic thromboembolism ( p = 0.78). Conclusion: Continuous and minimally-interrupted DOAC are both safe and non-inferior peri-procedural anticoagulation strategies compared with uninterrupted VKA for AF ablation. DOAC in general is associated with reduced major bleeding as demonstrated in pooled randomized studies. Highlights: Minimally-interrupted and continuous DOAC are both safe in AF ablation. DOAC has less major bleeding versus uninterrupted VKA in randomized studies. The risk of stroke is low regardless of anticoagulation strategy.